Towards an enhanced pipeline health monitoring system - optical fiber bragg grating (FBG) acoustic emission sensor - Yeo, Derek Chia Ching (2016)
Changes to the internal structure of pipe such as crack initiation and propagation will result in the abrupt redistribution of internal stress in which, causes acoustic emission (AE). Fibre Bragg Grating (FBG) has shown to be able to detect such AE events. FBG experiences a shift in its reflected wavelength (Bragg wavelength) when acoustic emission is present. Hence, FBG can be used to monitor the structural health of gas pipeline in real-time. In this thesis, the effect of the mounting orientation of FBG, mounting adhesive and FBG grating length on acoustic detection will be investigated. Based on the result obtained, FBG grating length has no immediate effect on the FBG ability to detect AE events whilst the other 2 parameters have caused an effect. A longer grating length however has shown to best mimic an acoustic detection of a conventional AE sensor. It was observed that best combination of parameters are mounting the FBG in longitudinal orientation, usage of long segment FBG and shear couplant mounting adhesive. The result obtained will be adopted for use to develop a holistic structural health monitoring system for the pipe. Monitoring algorithm will be incorporated in the system to allow real-time monitoring of structural health and immediate localisation of crack location.